The Impact of Content Marketing and Brand Trust On Customer Loyalty - Evi Yusniar Fog; Ricardo Indra (Syntax Corporation, 2022)
The increase in social media platforms in today's digital era and the understanding of companies or marketers about the importance of marketing products in marketing competition, as well as the importance of building relationships with customers to make them loyal customers, it makes company also use social media in building customer loyalty. Social media allows companies to do marketing and built direct relationships with consumers at a relatively small cost but with a higher efficiency value. However, given the amount of competition with similar products or services on social media, it is difficult for companies to reach potential target audiences on social media. Therefore, companies need to create content that attracts the target audience, so they may choose to use the products or services offering. Besides, compelling content allows the company to build its credibility on social media. In this context, marketing through content has a good impact on companies to increase trust and loyalty. This research aims to find out if the effect of content marketing and brand trust on customer loyalty. This research is expected to give insight to companies that use social media as a digital marketing strategies, to create creative, original, and useful content for social media users and ultimately build customer trust and lo.